2007
DOI: 10.5716/wp15422.pdf
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry on the interface of Orangutan conservation and sustainable livelihoods in Batang Toru (North Sumatra) ICRAF Working paper no. 56

Abstract: The Batang Toru area in North Sumatra supports the largest population of Sumatran Orangutan outside of formal conservation areas, as well as, a large human population. ICRAF and Winrock International analyzed the rich agroforestry livelihood systems of the area to: strengthen local support for conservation-based income alternatives to destructive forest practices; and catalyze local entrepreneurs to create sustainable economic alternative activities. The ICRAF-Winrock team conducted socioeconomic, land tenure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Розсадники дерев є важливим фактором успіху в багатьох втручаннях у розвиток лісового та сільського господарства [14].…”
Section: вступunclassified
“…Розсадники дерев є важливим фактором успіху в багатьох втручаннях у розвиток лісового та сільського господарства [14].…”
Section: вступunclassified
“…As production of the above tree commodity crops constitutes the most significant proportion of farm takings for tens of millions of tropical smallholders, investments in genetic improvement and better farm management of these crops have wide benefits (Mohan Jain and Priyadarshan, 2009). The successful promotion of higheryielding rubber clones and better managing plants to reduce input costs and retain some biodiversity in rubber agroforests have led to greater profits for many Indonesian smallholders (Wulan et al, 2006;Roshetko et al, 2007b). The rising price of cocoa in world markets has led to increased interest in upgrading smallholders' cocoa production methods in Indonesia, Côte d'Ivoire and elsewhere, through private-public partnerships involving the chocolate industry.…”
Section: Figurementioning
confidence: 99%
“…Widening oil palm cultivation is an example where a commodity crop causes both the loss of forest and of agrobiodiversity (Donald, 2004;Danielsen et al, 2009). Rubber agroforestry systems are compatible with habitat and biodiversity conservation (Wibawa et al, 2005;Beukema et al, 2007;Roshetko et al, 2007b), but they are, unfortunately, often a transient land use under pressure for conversion to less diverse agricultural systems (Ekadinata and Vincent, 2011). It has sometimes been suggested that intensive monocultures are on balance better than mixed production systems because they raise yields and hence reduce the amount of farmland needed for production, thus limiting the need to clear natural habitats for more agriculture.…”
Section: Tree Commodity Crops Displacement and Biodiversity Lossmentioning
confidence: 99%
“…Since 1936, only half of the Batang Toru watershed has been gazetted as state forest land (Figure 4 Current efforts to enhance orangutan conservation in the area need to consider the perspectives of the local stakeholders who are the de facto managers and protectors of the Batang Toru forested area. By ignoring valid local claims, particularly from communities who respect conservation, forestry authorities risk an escalation of tension and possible conflict that may make non-participatory, non-transparent conservation efforts counter-productive (Roshetko et al 2007b).…”
Section: Rapid Land Tenure Assessmentmentioning
confidence: 99%